Rolling out 5G : use cases, applications, and technology solutions - Badic, Biljana; Drewes, Christian; Karls, Ingolf; Mueck, Markus (Apress, 2016)
This concise book describes insufficiencies and challenges of 4G in the light of impending and crucial future communication needs, and provides lessons learned from an implementation and system operation perspective, and illustrates the way towards the next generation - 5G. Key changes and additions to 5G in terms of use cases, applications for and explorations of the technology are discussed. Rolling Out 5G: Use Cases, Applications, and Technology Solutions features detailed coverage of two critical topics - mmWave and spectrum sharing technologies including the evolution of LTE Advanced Pro. For the first time among 5G learning resources this book presents a holistic perspective on key ingredients for mobile communication in a 5G world. The authors are highly experienced experts in the field of wireless communications and related research that defines future technological trends. Their background ensures a unique look at long-term research, standardization and regulation, product design and marketization. This approach allows this much-needed book to capture the views of all key decision making stake-holders involved in the 5G definition process, and to serve readers in their roles connected with wireless communication's next generation of products and services.